Triptolide Shows High Sensitivity and Low Toxicity Against Acute Myeloid Leukemia Cell Lines Through Inhibiting WSTF-RNAPII Complex - Kang, Di; Liu, Yan; Song, Yi; Fang, Bingqian; Zhang, Qichun; Hu, Lihong (Frontiers in Oncology, 2022)
Triptolide exhibits superior and broad-spectrum antitumor activity. However, the narrow safety window caused by the toxicity of triptolide limits its clinical applications. Although several characterized targets for triptolide are reported, the association between triptolide and its targets in cancer therapy is not fully understood. Here, we show that acute myeloid leukemia (AML) cell lines are sensitive to triptolide by constructing an in vitro cell and in vivo xenograft models. Meanwhile, the triptolide-induced hepatotoxicity increases with increasing dosages within the xenograft models. Additionally, the expression levels of WSTF-RPB1 are strongly associated with the sensitivity to triptolide in hematological cancer cells and can be downregulated in a dose and time-dependent manner. Finally, we show that optimizing dosing regimens can achieve the same pharmaceutical effect and reduce toxicity. In summary, this study aims to search for triptolide-sensitive cell lines as well as the underlying molecular mechanisms in order to broaden the safety window of triptolide; thus, increasing its clinical utility.